2020
DOI: 10.1001/jamanetworkopen.2020.15943
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Age, Biomarkers, and Clinical History–Bleeding Risk Score in Patients With Atrial Fibrillation With Combined Aspirin and Anticoagulation Therapy Enrolled in the ARISTOTLE and RE-LY Trials

Abstract: Key Points Question Is the recently developed ABC (age, biomarkers, and clinical history)–bleeding risk score for patients with atrial fibrillation (AF) useful to identify patients with different risks of bleeding during concomitant aspirin and anticoagulation therapy? Findings This cohort study examined a total of 24 349 patients with AF from 2 randomized clinical trials and found that the ABC-bleeding risk score identified patients with different risks of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…The ABC (Atrial fibrillation Better Care) bleeding risk score, which includes blood biomarkers of bleeding including growth differentiation factor-15 (GDF-15), troponin T, and hemoglobin, has been shown to statistically better predict bleeding than clinical factor-based bleeding risk scores in patients with AF receiving OAC or taking both OAC and antiplatelet therapy (APT), and in different geographic regions, 43 44 45 46 but this was not confirmed in another study. 47 The consecutive addition of different blood-based biomarkers only slightly enhanced the predictive ability of the HAS-BLED score for major bleeding.…”
Section: Systematic Reviewmentioning
confidence: 93%
See 1 more Smart Citation
“…The ABC (Atrial fibrillation Better Care) bleeding risk score, which includes blood biomarkers of bleeding including growth differentiation factor-15 (GDF-15), troponin T, and hemoglobin, has been shown to statistically better predict bleeding than clinical factor-based bleeding risk scores in patients with AF receiving OAC or taking both OAC and antiplatelet therapy (APT), and in different geographic regions, 43 44 45 46 but this was not confirmed in another study. 47 The consecutive addition of different blood-based biomarkers only slightly enhanced the predictive ability of the HAS-BLED score for major bleeding.…”
Section: Systematic Reviewmentioning
confidence: 93%
“…26 A Taiwanese registry of 24,990 AF patients showed that by 1 year, around 21% had acquired at least one new bleeding risk factor, including hypertension (5.84%), stroke (5.33%), bleeding (5.06%), concomitant use of antiplatelet agents or NSAIDs (4.34%), and renal (3.08%) or liver (2.22%) impairment. 28 Data from ORBIT AF shows that over a 2-year follow-up, about a quarter of patients had >20% decline in estimated glomerular filtration rate (eGFR) and The ABC (Atrial fibrillation Better Care) bleeding risk score, which includes blood biomarkers of bleeding including growth differentiation factor-15 (GDF-15), troponin T, and hemoglobin, has been shown to statistically better predict bleeding than clinical factor-based bleeding risk scores in patients with AF receiving OAC or taking both OAC and antiplatelet therapy (APT), and in different geographic regions, [43][44][45][46] but this was not confirmed in another study. 47 The consecutive addition of different blood-based biomarkers only slightly enhanced the predictive ability of the HAS-BLED score for major bleeding.…”
Section: Dynamic and Modifiable Nature Of Bleeding Riskmentioning
confidence: 99%
“…Growth differentiation factor-15 (GDF-15) is a novel cardiac biomarker [2,3], a strong predictor of bleeding in patients with NVAF, and evaluates bleeding, stroke, and death risk in atrial fibrillation (AF) [4][5][6]. Studies [6][7][8] showed that GDF-15 has better stability and continuity as a novel cardiac biomarker, which has become a hotspot of clinical research for bleeding risk evaluation and clinical application in patients with atrial fibrillation [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Growth differentiation factor-15 (GDF-15) is a novel cardiac biomarker [2,3], a strong predictor of bleeding in patients with NVAF, and evaluates bleeding, stroke, and death risk in atrial fibrillation (AF) [4][5][6]. Studies [6][7][8] showed that GDF-15 has better stability and continuity as a novel cardiac biomarker, which has become a hotspot of clinical research for bleeding risk evaluation and clinical application in patients with atrial fibrillation [9,10]. e novel ABC (age, biomarkers, and clinical history) AF bleeding risk scores outperform the HAS-BLED bleeding risk score for major bleeding (MB) patients with NVAF receiving oral anti-coagulation in the clinical trial cohort such as ARISTOTLE [6], RE-LY [6], and ENGAGE AF-TIMI 48 [8] indicated that the ABC-AF bleeding risk score outperformed the traditional HAS-BLED score.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation